-
Notifications
You must be signed in to change notification settings - Fork 6
/
Copy pathtermWork
1665 lines (1453 loc) · 105 KB
/
termWork
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
563
564
565
566
567
568
569
570
571
572
573
574
575
576
577
578
579
580
581
582
583
584
585
586
587
588
589
590
591
592
593
594
595
596
597
598
599
600
601
602
603
604
605
606
607
608
609
610
611
612
613
614
615
616
617
618
619
620
621
622
623
624
625
626
627
628
629
630
631
632
633
634
635
636
637
638
639
640
641
642
643
644
645
646
647
648
649
650
651
652
653
654
655
656
657
658
659
660
661
662
663
664
665
666
667
668
669
670
671
672
673
674
675
676
677
678
679
680
681
682
683
684
685
686
687
688
689
690
691
692
693
694
695
696
697
698
699
700
701
702
703
704
705
706
707
708
709
710
711
712
713
714
715
716
717
718
719
720
721
722
723
724
725
726
727
728
729
730
731
732
733
734
735
736
737
738
739
740
741
742
743
744
745
746
747
748
749
750
751
752
753
754
755
756
757
758
759
760
761
762
763
764
765
766
767
768
769
770
771
772
773
774
775
776
777
778
779
780
781
782
783
784
785
786
787
788
789
790
791
792
793
794
795
796
797
798
799
800
801
802
803
804
805
806
807
808
809
810
811
812
813
814
815
816
817
818
819
820
821
822
823
824
825
826
827
828
829
830
831
832
833
834
835
836
837
838
839
840
841
842
843
844
845
846
847
848
849
850
851
852
853
854
855
856
857
858
859
860
861
862
863
864
865
866
867
868
869
870
871
872
873
874
875
876
877
878
879
880
881
882
883
884
885
886
887
888
889
890
891
892
893
894
895
896
897
898
899
900
901
902
903
904
905
906
907
908
909
910
911
912
913
914
915
916
917
918
919
920
921
922
923
924
925
926
927
928
929
930
931
932
933
934
935
936
937
938
939
940
941
942
943
944
945
946
947
948
949
950
951
952
953
954
955
956
957
958
959
960
961
962
963
964
965
966
967
968
969
970
971
972
973
974
975
976
977
978
979
980
981
982
983
984
985
986
987
988
989
990
991
992
993
994
995
996
997
998
999
1000
\documentclass[titlepage]{article}
\usepackage[utf8x]{inputenc}
\usepackage{amsthm, amsmath, amsfonts, amssymb, mathrsfs,mathabx}
\usepackage{chngcntr}
\usepackage{mdframed}
\usepackage{breqn}
\usepackage{tikzsymbols}
\setcounter{section}{+1}
\DeclareMathOperator*{\Pwr}{\mathscr{P}}
\DeclareMathOperator*{\Rcal}{\mathcal{R}}
\DeclareMathOperator*{\Ima}{Im}
\DeclareMathOperator*{\dom}{dom}
\DeclareMathOperator*{\card}{card}
\DeclareMathOperator*{\ord}{ord}
\newtheorem{exercise}{\underline{Exercise}}[section]
\newtheorem{proposition}{\textit{Proposition}}[section]
\renewcommand{\qedsymbol}{\Summertree[1]}
\newtheorem{lemma}{\textit{Lemma}}[section]
\newtheorem{corollary}{\textit{Corollary}}[section]
\newenvironment{Lemma}[1][Lemma]{\proof[#1]\leftskip=1cm\rightskip=1cm}{\endproof}
\usepackage[linktocpage=true]{hyperref}
\usepackage{etoolbox}
\expandafter\patchcmd\csname\string\corollary\endcsname
{\normalparindent}{0pt }{}{}
\newcommand{\bij}{\mathrel{\hookrightarrow\hspace{-1.8ex}\to}}
\counterwithin*{equation}{section}
\counterwithin*{equation}{subsection}
\title{Set Theory Term Work}
\author{Blikas }
\date{September 2015}
\begin{document}
\maketitle
\tableofcontents
\newpage
\begin{mdframed}
\section{Misc. Exersizes}
\end{mdframed}
\bigbreak
\subsection{Logical Operators}
\begin{exercise}We show that $\land$, $\lor$ are commutative. We do this via truth table.
\end{exercise}
\begin{proof} Consider the logical sentences $p$, $q$ and the following truth table:
\begin{center}
\begin{tabular}{c|c|c|c}
$p$ & $q$ & $p \lor q$ & $q \lor p$\\
T & T & T & T \\
T & F & T & T \\
F & T & T & T \\
F & F & F & F
\end{tabular}
\end{center}
Thus, $p \lor q \iff q \lor p $
\end{proof}
\begin{proof} Consider the logical sentences $p$ and $q$ and the following truth table:
\begin{center}
\begin{tabular}{c|c|c|c}
$p$ & $q$ & $p \land q$ & $q \land p$\\
T & T & T & T \\
T & F & F & F \\
F & T & F & F \\
F & F & F & F
\end{tabular}
\end{center}
Thus, $p \land q \iff q \land p$.
\end{proof}
\newpage
\subsection{Logical Rules}
\begin{exercise}We show that $p \lor p \iff p$ and $p \land p \iff p$, via truth table.
\end{exercise}
\begin{proof}
Consider the logical sentence $p$ and the following truth table:
\begin{center}
\begin{tabular}{c|c}
$p$ & $p \lor p$\\
T & T \\
F & F
\end{tabular}
\end{center}
Thus, $p \lor p \iff p$
\end{proof}
\begin{proof} Consider the logical sentence $p$ and the following truth table:
\begin{center}
\begin{tabular}{c|c}
$p$ & $p \land p$\\
T & T \\
F & F
\end{tabular}
\end{center}
Thus, $p \iff p \land p$.
\end{proof}
\begin{exercise}
We show that $p \Rightarrow p \lor q$ via truth table.
\end{exercise}
\begin{proof} Consider the logical sentences $p$ and $q$ and the following truth table:
\begin{center}
\begin{tabular}{c|c|c}
$p$ & $q$ & $p \lor q$ \\
T & T & T \\
T & F & T \\
F & T & T \\
F & F & F
\end{tabular}
\end{center}
Thus, if $p$ is true, $p \lor q$ is true, i.e. $p \Rightarrow p \lor q$.
\end{proof}
\newpage
\begin{mdframed}
\section{Unordered Pairs}
\end{mdframed}
\begin{exercise} Consider the sets $ \emptyset $, $ \lbrace \emptyset \rbrace $, $ \lbrace \lbrace \emptyset \rbrace \rbrace$, etc.; Consider all the pairs such as $ \lbrace \emptyset, \lbrace \emptyset \rbrace \rbrace$, formed by two of them; consider the pairs formed by any such two pairs, or else mixed pairs formed by a singleton and any pair; and proceed \textit{ad infinitum}. Are all the sets obtained in this way distinct from one another?
\end{exercise}
\bigbreak
Yes, all sets obtained in this way are distinct.
\begin{proof}
By the axiom of pairing, we can form $A$ and $B$ as given, and by the axiom of specification, they are the only such sets which contain their elements. Suppose, to the contrary, that $A=B$.
\par If $A=B$, then for all $a \in A$, $a \in B$, and for all $b \in B$, $b \in A$. Now, either $A$ and $B$ are singletons, or they are pairs.
\begin{itemize}
\item \textit{$A$ and $B$ are singletons:} Say, $A = \{a\}$, and $B = \{b\}$. Thus, by the \textit{Axiom of Extension}, we have $a = b$. Implying that $A$ and $B$ were formed in the same way.
\item \textit{$A$ and $B$ are pairs:} Let $A = \{a, a'\}$, $B = \{b,b'\}$. Without loss of generality, suppose that $a = b$, and $a' = b'$. If this is the case, then by the \textit{Axiom of Extension}, again, we have that $a,b$ were obtained in the same fashion, as well as $a',b'$. But in this case, $A$ and $B$ were constructed in the same manner.
\end{itemize}
Either way, we have a contradiction. Thus, $A$ and $B$ are formed distinctly.
\end{proof}
\newpage
\begin{mdframed}
\section{Unions and Intersections}
\end{mdframed}
Throughout these exercises we consider a arbitrary non-empty collection $\mathcal{C}$, of sets. For simplicity we will assume that $ \mathcal{C}= \{ A, B, C\}$ for arbitrary non-empty sets (unless specified) $A$, $B$, $C$ and will make liberal use of the notation $\{x: S(x)\}$, in-place of the more precises yet cumbersome notation $\{x \in \bigcup \mathcal{C}: S(x) \}$.
\begin{exercise} We show the following:
\begin{align}
A \cup \emptyset & = A \\
A \cup B & = B \cup A \\
A \cup (B \cup C) & = (A \cup B) \cup C\\
A \cup A & = A \\
A \subset B \iff A \cup B & = B
\end{align}
\end{exercise}
\begin{proof} ($\iff$)
Since $\emptyset$ has no elements, for all $a \in \bigcup \mathcal{C}$, $a \notin \emptyset$ and we have,
\begin{align*}
x \in A \cup \emptyset = \lbrace x: x \in A \lor x \in \emptyset \rbrace & \iff x \in A \lor x \in \emptyset = \lbrace \rbrace \\
& \iff x \in A
\end{align*}
Thus, $A \cup \emptyset = A$
\end{proof}
\begin{proof} ($\iff$)
\bigbreak
$$A \cup B = \lbrace x : x \in A \lor x \in B \rbrace = \lbrace x : x \in B \lor x \in A \rbrace = B \cup A$$
\end{proof}
\begin{proof} ($\iff$)
\bigbreak
\begin{equation*}
\begin{split}
x \in A \cup (B \cup C) & \iff x \in A \lor x \in B \cup C \\
&\iff x \in A \lor x \in B \lor x \in C \\
& \iff x \in \lbrace x : x \in A \lor x \in B \rbrace \lor x \in C \\
& \iff x \in A \cup B \lor x \in C \\
& \iff x \in (A \cup B) \cup C
\end{split}
\end{equation*}
\end{proof}
\begin{proof} ($\iff$)
\bigbreak
$$ A \cup A = \lbrace x: x \in A \lor x \in A\rbrace = \lbrace x: x \in A \rbrace = A$$
\end{proof}
\begin{proof}
$ $\newline
($\Rightarrow$) We note that $A \subset B$ iff for all $x \in A$, $x \in B$. Thus, we have that $$x \in A \cup B = \{ x: x \in A \lor x \in B \} \Rightarrow x \in A \lor x \in B \Rightarrow x \in B$$ by the comments above. And likewise, $$x \in B \Rightarrow x \in B \lor x \in A \Rightarrow x \in \{ x: x \in A \lor x \in B \} \Rightarrow x \in A \cup B$$ That is, $A \cup B = B$.
$ $\newline
($\Leftarrow$)
Suppose $A \cup B = B$. Then, $$x \in A \Rightarrow x \in \{ x : x \in A \cup x \in B\} = A \cup B = B$$ That is, $A \subset B$.
\end{proof}
\setcounter{equation}{0}
\begin{exercise} We show the following:
\begin{align}
A \cap \emptyset & = \emptyset \\
A \cap B & = B \cap A \\
A \cap (B \cap C) & = (A \cap B) \cap C \\
A \cap A & = A \\
A \subset B \iff A \cap B & = A \\
\end{align}
\end{exercise}
\begin{proof} (1) Suppose that $A \neq \emptyset$, then
\bigbreak
$ $\newline
($\Rightarrow$)
\begin{align*}
x \in A \cap \emptyset = \{ x: x\in A \land x \in \emptyset \} & \Rightarrow x \in \emptyset \land x \in A \\
& \Rightarrow x \in \emptyset
\end{align*}
$ $\newline
($\Leftarrow$)
\begin{align*}
& (\emptyset \subset A) \land (\emptyset \subset \emptyset) \\
& \Rightarrow \emptyset \subset A \cap \emptyset \\
\end{align*}
\end{proof}
\begin{proof}(2) ($\iff$)
\bigbreak
$$A \cap B = \{ x: x\in A \land x\in B\} = \{ x: x \in B \land x \in A \} = B \cap A$$
\end{proof}
\begin{proof}(3) ($\iff$)
$ $\newline
\begin{align*}
x \in A \cap (B \cap C) & \iff x \in A \land x \in B \cap C = \{ x: x \in B \land x \in C \} \\
& \iff x \in A \land x \in B \land x \in C \\
& \iff x \in \{x: x \in A \land x\in B\} \land x \in C \\
& \iff x \in A \cap B \land x \in C \\
& \iff x \in (A \cap B) \cap C
\end{align*}
\end{proof}
\begin{proof}(4) ($\iff$)
$ $\newline
$$A \cap A = \{x: x \in A \land x \in A \} = \{x: x \in A\} = A$$
\end{proof}
\begin{proof}(5)
$ $\newline
($\Rightarrow$) Suppose that $A,B \neq \emptyset$. We note that $A \subset B$ iff for all $x \in A$, $x \in B$; then,
$$x \in A \Rightarrow x \in B \Rightarrow x \in A \land x \in B \Rightarrow x \in A \cap B$$ And likewise,
$$x \in A \cap B = \{x: x\in A \land x \in B \} \Rightarrow x \in A \land x \in B \Rightarrow x \in A$$ That is, $A \cap B = A$.
$ $\newline
($ \Leftarrow$)Suppose that $A \cap B = A$. Then,
$$x \in A \Rightarrow x \in A \cap B = \{ x: x \in A \land x \in B\} \Rightarrow x \in A \land x \in B \Rightarrow x \in B$$ That is, $A \subset B$.
\end{proof}
\setcounter{equation}{0}
\begin{exercise} We wish show that $(A \cap B) \cup C = A \cap (B \cup C) \iff C \subset A$: We first show (1) in the following, noting that (2) was proved in the text;
$ $\newline
From page fifteen,
\begin{equation}
A \cap (B \cup B) = (A \cap B) \cup (A \cap C)
\end{equation}
and,
\begin{equation}
A \cup (B \cap C) = (A \cup B) \cap (A \cup C)
\end{equation}
\end{exercise}
\begin{proof} ($\Rightarrow$)
\bigbreak
$ $\newline
Suppose that not all of $A$, $B$, $C$ are the emptyset. Then,
$$x \in A \cap (B \cup C) \Rightarrow x \in A \land x \in B \cup C$$ Now, either $x \in B$ or $x \in C$:
\begin{equation*}
x \in B \land x \in A \Rightarrow x \in A \cap B \Rightarrow (A \cap B) \cup (A \cap C)
\end{equation*}
\begin{equation*}
x \in C \land x \in A \Rightarrow x \in A \cap C \Rightarrow (A \cap B) \cup (A \cap C)
\end{equation*}
$ $\newline
Either way, $x \in (A \cap B) \cup (A \cap C)$. To prove the reverse inclusion, we note that similar logic holds; either $x \in A \cap B$ or $x \in A \cap C$.
\end{proof}
\bigbreak
$ $\newline
Now, we show that $(A \cap B) \cup C = A \cap (B \cup C) \iff C \subset A$:
\begin{proof}
\bigbreak
$ $\newline
($\Leftarrow$)
\bigbreak
$ $\newline
Suppose that $C \subset A$. Then, for all $x \in C$, $x \in A$; By \textit{Exercise 4.1.5} and the proof above, we have the following:
\begin{equation}
(A \cap B) \cup C = (A \cup C) \cap (B \cup C) = A \cap (B \cup C)
\end{equation}
$ $\newline
($\Rightarrow$)
$ $\newline
Suppose that $(A \cap B) \cup C = A \cap (B \cup C)$. Then,
\begin{equation*}
\begin{split}
x \in C & \Rightarrow x \in \{x: x \in A \cap B \lor x \in C \} \\
& = (A \cap B) \cup C \\
& = A \cap (B \cup C)
\end{split}
\end{equation*} by the assumption. Thus,
\begin{equation*}
\begin{split}
x \in C & \Rightarrow x \in A \cap (B \cup C) \\
& \Rightarrow x \in A \land x \in B \cup C \\
& \Rightarrow x \in A
\end{split}
\end{equation*}
That is, $C \subset A$.
\end{proof}
\newpage
\begin{mdframed}
\section{Complements and Powers}
\end{mdframed}
$ $\newline
Throughout these exercises we assume that "all sets are subsets of one and the same set $\mathcal{E}$, and that all complements (unless otherwise specified) are formed relative to that $\mathcal{E}$" (Halmos). Likewise, we will often use the more convenient, yet less accurate notation $\{x: S(x)\}$ in place of $\{x \in \mathcal{E}: S(x)\}$
\setcounter{equation}{0}
\begin{exercise}We prove the following:
\begin{align}
A - B & = A \cap B^{c} \\
A \subset B & \iff A - B = \emptyset \\
A - ( A - B) & = A \cap B \\
A \cap (A - C) & = (A \cap B) - (A \cap C)\\
A \cap B & \subset (A \cap C) \cup (B \cap C^{c}) \\
(A \cup C) \cap (B \cup C^{c}) & \subset A \cup B \\
\end{align}
\end{exercise}
\begin{proof} (1) ($\iff$)
\bigbreak
\begin{equation*}
\begin{split}
A - B & = \{x \in \mathcal{E}: x \in A \land x \notin B \} \\
& \iff x \in A \land x \notin B \\
& \iff x \in A \land x \in B^c \\
& \iff x \in A \cap B^c
\end{split}
\end{equation*}
\end{proof}
\begin{proof} (2)
$ $\newline
$ $\newline
($\Rightarrow$) Suppose that $A - B \neq \emptyset$, but $A \subset B$; since $A \subset B$, if $x \in A$, $x \in B$. Thus, if $x \in A - B = \{ x \in \mathcal{E}: x \in A \land x \notin B\}$, $x \notin B$. However $x \in A$, which implies $x \in B$: A contradiction.
$ $\newline
\bigbreak
$ $\newline
($\Leftarrow$) Suppose that $A - B = \emptyset$ and that there exists some $x \in A$ which is not in $B$, i.e. $A \not\subset B$. However this is a contradiction since $$x \in A \land x \notin B \Rightarrow x \in \{x \in \mathcal{E}: x \in A \land x \notin B \} = A - B$$ and yet $A -B = \emptyset$.
\end{proof}
\begin{proof} (3) ($\iff$)
\bigbreak
By the proof above,
\begin{equation*}
\begin{split}
A - (A - B) & = A - (A \cap B^c) = \{x \in \mathcal{E}: x \in A \land x \notin A \cap B^c\} \\
& \iff x \in A \land x \notin A \cap B^c \\
& \iff x \in A \land x \notin B^c \\
& \iff x \in A \land x \in B \\
& \iff x \in \{x \in \mathcal{E}: x \in A \land x \in B\} = A \cap B
\end{split}
\end{equation*}
\end{proof}
\begin{proof} (4) ($\iff$)
\bigbreak
\begin{equation*}
\begin{split}
x \in A \cap (B - C) & \iff x \in A \land x \in (B-C) \\
& \iff x \in A \land x \in \{ x \in \mathcal{E}: x \in B \land x \notin C \} \\
& \iff x \in A \land x \in B \land x \notin C \\
& \iff x \notin \{ x \in \mathcal{E}: x \in A \land x \in C \} \land x \in A \cap B \\
& \iff x \notin A \cap C \land x \in A \cap B \\
& \iff x \in \{ x \in \mathcal{E}: x \notin A \cap C \land x \in A \cap B \} \\
& \iff x \in (A \cap B) - (A \cap C)
\end{split}
\end{equation*}
\end{proof}
\setcounter{equation}{0}
\begin{proof} (5) ($\Rightarrow$)
\bigbreak
Consider $C \in \bigcup \mathcal{C}$, as stated above.
\begin{equation}
\begin{split}
x \in A \cap B & \Rightarrow x \in \{ x \in \mathcal{E}: x \in A \land x \in B \} \\
& \Rightarrow x \in A \land x \in B \\
& \Rightarrow (x \in A \land x \in B) \land (x \in C \lor x \in C^c)
\end{split}
\end{equation}
\begin{equation}
\begin{split}
x \in C \land (1) & \Rightarrow x \in A \cap C \land x \in B \cap C
\end{split}
\end{equation}
\begin{equation}
\begin{split}
x \in C^c \land (1) & \Rightarrow x \in A \cap C^c \land x \in B \cap C^c
\end{split}
\end{equation}
$ $\newline
Thus, either way, $x \in (A \cap C)$ or $x \in (B \cap C^c)$, i.e. $x \in (A \cap C) \cup (A \cap C^c)$
\end{proof}
\setcounter{equation}{0}
\begin{proof} (6) ($\Rightarrow$)
\bigbreak
\begin{equation}
\begin{split}
x \in (A \cup C) \cap (B \cup C^c) & \Rightarrow x \in A \cup C \land x \in B \cup C^c \\
& \Rightarrow (x \in A \lor x \in C) \land (x \in B \lor x \in C^c)
\end{split}
\end{equation}
$ $\newline
We note that either $x \in C$, or $x \in C^c$:
\begin{equation}
\begin{split}
x \in C \land (1) & \Rightarrow x \notin C^c \land (x \in B \lor x \in A) \\
& \Rightarrow x \in A \cup B
\end{split}
\end{equation}
\begin{equation}
\begin{split}
x \in C^c \land (1) & \Rightarrow x \notin C \land (x \in A \lor x \in B) \\
&\Rightarrow x \in A \cup B
\end{split}
\end{equation}
$ $\newline
Either way, $x \in A \cup B$.
\end{proof}
\begin{exercise} We show that $\mathscr{P}(E) \cap \mathscr{P}(F)= \mathscr{P}(E \cap F)$:
\end{exercise}
\begin{proof}
Let $E$, $F$ be sets such that $E$, $F \subset \mathcal{E}$ ; via \textit{Axiom of Powers}, $\mathscr{P}(E)$, $\mathscr{P}(F)$; specifically, from the discussion in Halmos\footnote{Halmos, P. "\textit{Naive Set Theory}". pg 19}, $\mathscr{P}(E) = \{X: X \subset E\}$, and $\mathscr{P}(F) = \{X: X \subset F\}$. Then, we have the following:
\setcounter{equation}{0}
\begin{equation*}
\begin{split}
X \in \mathscr{P}(E) \cap \mathscr{P}(F) & \iff X \in \mathscr{P}(E) \land X \in \mathscr{P}(F) \\
& \iff X \in \{Y: Y \subset E \land Y \subset F \} \\
& \iff X \subset E \land X \subset F \\
& \iff \forall x( x \in X \Rightarrow (x \in E \land x \in F) )\\
& \iff \forall x \in X, x \in E \cap F \\
& \iff X = \{x \in \mathcal{E}: x \in X \} \subset E \cap F \\
& \iff X \in \{Y: Y \subset E \cap F \} \\
& = \mathscr{P}(E \cap F)
\end{split}
\end{equation*}
\end{proof}
\begin{exercise} We show that $\mathscr{P}(E) \cup \mathscr{P}(F) \subset \mathscr{P}(E \cup F)$:
\end{exercise}
\begin{proof}
Let $E$, $F$ be given as in the discussion of proof \textit{5.2.0}. We first claim that if $A$, $B$ are sets, then ($x \subset A \lor x \subset B \Rightarrow x \subset A \cup B$). Indeed; if $x \subset A$, then $x \subset A \cup B$ and likewise, $x \subset B$ implies $x \subset B \cup A$. With this in mind, we have the following:
\begin{equation*}
\begin{split}
X \in \mathscr{P}(E) \cup \mathscr{P}(F) & = \{X: X \in \mathscr{P}(E) \lor X \in \mathscr{P}(F) \} \\
& \iff X \in \mathscr{P}(E) \lor X \in \mathscr{P}(F) \\
& \iff X \in \{Y: Y \subset E \} \lor X \in \{Y: Y \subset F \} \\
& \iff X \in \{Y: Y \subset E \lor Y \subset F \} \\
& \Rightarrow X \in \{Y: Y \subset E \cup F \} \\
& = \mathscr{P}(E \cup F)
\end{split}
\end{equation*}
\end{proof}
\begin{exercise} We show that $\bigcap_{X \in \mathcal{C}} \mathscr{P}(X) = \mathscr{P}(\bigcap_{X \in \mathcal{C}} X)$:
\end{exercise}
\begin{proof} Let $\mathcal{C}$ be a non-empty collection of sets.
\bigbreak
($\Rightarrow$)
\begin{equation*}
\begin{split}
z \in \bigcap_{X \in \mathcal{C}} \mathscr{P}(X) & \Rightarrow (\forall X \in \mathcal{C})(z \in \mathscr{P}(X)) \\
& \Rightarrow (\forall X \in \mathcal{C})(\{z\} \subset \mathscr{P}(X)) \\
& \Rightarrow (\forall X \in \mathcal{C})(z \in X) \\
& \Rightarrow z \in \bigcap_{X \in \mathcal{C}} X \\
& \Rightarrow \{z\} \subset \bigcap_{X \in \mathcal{C}} X \\
& \Rightarrow z \in \mathscr{P} (\bigcap_{X \in \mathcal{C}} X)
\end{split}
\end{equation*}
\bigbreak
($\Leftarrow$)
\begin{equation*}
\begin{split}
z \in \mathscr{P}(\bigcap_{X \in \mathcal{C}} X) & \Rightarrow z \in \{Y: Y \subset \bigcap_{X \in \mathcal{C}} X\} \\
& \Rightarrow z \subset \bigcap_{X \in \mathcal{C}} X \\
& \Rightarrow (\forall X \in \mathcal{C})(z \subset X) \\
& \Rightarrow (\forall X \in \mathcal{C})(\forall v \in z)(v \in X) \\
& \Rightarrow (\forall X \in \mathcal{C})(\forall v \in z)(\{v\} \subset \mathscr{P}(X))\\
& \Rightarrow (\forall X \in \mathcal{C})(\forall v \in z)(v \in \mathscr{P}(X))\\
& \Rightarrow (\forall X \in \mathcal{C})(z \in \mathscr{P}(X)) \\
& \Rightarrow z \in \bigcap_{X \in \mathcal{C}} \mathscr{P}(X)
\end{split}
\end{equation*}
And this completes the proof.
\end{proof}
\begin{exercise}We show that $\bigcup_{X \in \mathcal{C}} \mathscr{P}(X) \subset \mathscr{P}(\bigcup_{X \in C} X)$:
\end{exercise}
\begin{proof}
Let $\mathcal{C}$ be a collection of sets. A common fact used in the following proof is that if $x \in \mathscr{P}(X)$, then $x \subset X$ for any set $X$. This is indeed true, since $\mathscr{P}(X)= \{Y: Y \subset X\}$. With this in mind, we have
\begin{equation*}
\begin{split}
z \in \bigcup_{X \in \mathcal{C}} \mathscr{P}(X) & \Rightarrow (\exists Y \in \mathcal{C})(z \in \mathscr{P}(Y)) \\
& \Rightarrow z \subset Y \in \mathcal{C} \\
& \Rightarrow z \subset \{x: x \in X (\forall X \in \mathcal{C}) \} = \bigcup_{X \in \mathcal{C}}X \\
& \Rightarrow (\forall s \in z)(s \in \bigcup_{X \in \mathcal{C}}X) \\
& \Rightarrow (\forall s \in z)(s \in \mathscr{P}(\bigcup_{X \in \mathcal{C}}X)) \\
& \Rightarrow z \in \mathscr{P}(\bigcup_{X \in \mathcal{C}}X)
\end{split}
\end{equation*}
Which completes the proof.
\end{proof}
\begin{exercise}We show that $\bigcap_{X \in \mathscr{P}(E)}X = \emptyset$:
\end{exercise}
\begin{proof}
Let $E$ be a set and consider $\mathscr{P}(E) = \{Y: Y \subset E\}$. We note that this is non-empty because $\emptyset \in \Pwr (E)$, since $\emptyset$ is a subset of every set. We also note that the statement ($x \in \emptyset \Rightarrow x \in \bigcap_{X \in \mathscr{P}(E)}X$) is vacuously satisfied since $\emptyset$ has no elements. Thus, we only show the forward inclusion:
\bigbreak
($\Rightarrow$)
\begin{equation*}
\begin{split}
x \in \bigcap_{X \in \mathscr{P}(E)}X & \Rightarrow (\forall X \in \Pwr(E))(x \in X) \\
& \Rightarrow x \in \emptyset \in \Pwr (E)
\end{split}
\end{equation*} And this completes the proof.
\end{proof}
\begin{exercise}We show that ($E \subset F \Rightarrow \Pwr(E) \subset \Pwr(F)$):
\end{exercise}
\begin{proof}
Suppose that $E \subset F$ for sets $E$, $F$. Then, we have the following:
\begin{align*}
e \in \Pwr (E) & \Rightarrow e \subset E &\\
& \Rightarrow (\forall x \in e)(x \in E) &\\
& \Rightarrow (\forall x \in e)(x \in F) &(\text{by Assumption})\\
& \Rightarrow e \subset F &\\
& \Rightarrow e \in \Pwr(F) &(\text{by Definition}) \\
\end{align*} Which completes the proof.
\end{proof}
\begin{exercise}We show that $E = \bigcup \Pwr(E) = \bigcup_{X \in \Pwr(E)}X$:
\end{exercise}
\begin{proof}
Let $E$ be a set. Then, we have the following:
\bigbreak
($\Leftarrow$)
\begin{align*}
x \in \bigcup \Pwr(E) & \Rightarrow (\exists Y \in \Pwr(E))(x \in Y) \\
& \Rightarrow x \in Y \subset E \\
& \Rightarrow x \in E
\end{align*}
\bigbreak
($\Rightarrow$)
\begin{align*}
x \in E & \Rightarrow \{x\} \in \Pwr(E) \\
& \Rightarrow x \in \{x\} \in \Pwr(E) \\
& \Rightarrow x \in \bigcup \{X: X \in \Pwr(E) \} \\
& = \bigcup \Pwr(E) \\
\end{align*}
Which completes the proof.
\end{proof}
\begin{exercise} We show that $\mathscr{P}\Big(\bigcup E\Big)$ is a set that includes $E$, typically, as a proper subset.
\end{exercise}
\begin{proof} Indeed, $\mathscr{P}\Big(\bigcup E\Big) = \mathscr{P}(E) = \{X \in E: X \subset E\}$. If $E$ is non-empty, then it is clear that $E \subsetneq \mathscr{P}(E)$. However, if $E = \emptyset$, then $\Pwr(E) = \emptyset$ and $E = \Pwr(E)$.
\end{proof}
\newpage
\begin{mdframed}
\section{Ordered Pairs}
\end{mdframed}
Throughout this section, we will consider $A$, $B$, $C$, $X$, $Y$ to be any sets, and will use the notation
$\{x: S(x)\}$ in place of the more accurate, yet cumbersome notation $\{x \in \bigcup \mathcal{C}: S(x)\}$.
\bigbreak
\begin{exercise} We show the following:
\setcounter{equation}{0}
\begin{align}
(A \cup B) \times X & = (A \times X) \cup (B \times X) \\
(A \cap B) \times (X \cap Y) & = (A \times X) \cap (B \times Y) \\
(A - B) \times X & = (A \times X) - (B \times X)\\
(A = \emptyset \lor B = \emptyset) & \iff (A \times B = \emptyset)\\
(A \subset X) \land (B \subset Y) & \iff (A \times X \subset X \times Y)
\end{align}
\end{exercise}
\begin{proof} (1)
\bigbreak ($\Rightarrow$)
\begin{align*}
(x,y) \in (A \cup B) \times X & \iff (x,y) \in \{(a,b): a \in A \cup B \land b \in X \} \\
& \iff x \in A \cup B \land y \in X \\
& \iff (x \in A \lor x \in B) \land y \in X \\
(\text{by Distributivity}) \quad & \iff (x \in A \land y \in X) \lor (x\in B \land y\in X) \\
& \Rightarrow (x \in A \cup X \land y \in A \cup X) \lor (x \in B \cup X \land y \in B \cup X) \\
(\text{by Remarks in Text}) \quad & \Rightarrow \{x, \{x,y\} \} \subset \mathscr{P}(A \cup X)
\lor \{x, \{x,y\} \} \subset \Pwr(B \cup X) \\
& \iff (x,y) \in \Pwr(\Pwr(A \cup X)) \lor (x,y) \in \Pwr(\Pwr(B \cup X)) \\
(\text{by Remarks in Text}) \quad & \iff (x,y) \in (A \times X) \cup (B \times X) \\
\end{align*}
\bigbreak ($\Leftarrow$)
\begin{align*}
(x,y) \in (A \times X) \cup (B \times X) & \iff (x,y) \in (A \times X) \lor (x,y) \in (B \times X) \\
(\text{by Definition}) \quad & \Rightarrow (x \in A \land y \in X) \lor (x \in B \land y \in X) \\
& \iff (x \in A \lor x \in B) \land y \in X \\
& \iff x \in A \cup B \land y \in X \\
& \Rightarrow x \in (A \cup B) \cup X \land y \in (A \cup B) \cup X \\
& \Rightarrow \{ \{x\}, \{x,y\} \} \subset \Pwr((A \cup B) \cup X) \\
& \iff \{ \{x\}, \{x,y\} \} \in \Pwr(\Pwr((A \cup B) \cup X)) \\
& \Rightarrow (x,y) \in (A \cup B) \times X\\
\end{align*}
Which completes the proof.
\end{proof}
\bigbreak
\begin{proof}(2)
\bigbreak
($\Rightarrow$)
\begin{align*}
(c,d) \in (A \cap B) \times (X \cap Y) & \iff c \in A \cap B \land d \in X \cap Y \\
& \iff (c \in A \land c \in B) \land (d \in X \land d \in Y) \\
(\text{by Commutativity}) \quad & \iff (c \in A \land d \in X) \land (c \in B \land d \in Y) \\
& \Rightarrow (c \in A \cup X \land d \in A \cup X) \land (c \in B \cup Y \land d \in B \cup Y)\\
& \Rightarrow \{ \{c\},\{c,d\} \} \subset \Pwr(A \cup X) \land \{ \{c\},\{c,d\} \} \subset \Pwr(B \cup Y) \\
& \iff (c,d) \in \Pwr(\Pwr(A \cup X)) \land (c,d) \in \Pwr(\Pwr(B \cup X)) \\
& \iff (c,d) \in A \times X \land (c,d) \in B \times X \\
& \iff (c,d) \in (A \times X) \cap (B \times X) \\
\end{align*}
\bigbreak
($\Leftarrow$)
\begin{align*}
(c,d) \in (A \times X) \cap (B \times X) & \iff (c,d) \in (A \times X) \land (c,d) \in (B \times X)\\
& \iff (c \in A \land d \in X) \land (c \in B \land d \in X) \\
(\text{by Commutativity}) \quad & \iff (c \in A \land c \in B) \land d \in X \\
& \iff (c \in (A \cap B)) \land d \in X \\
& \Rightarrow c \in (A \cap B) \cup X \land d \in (A \cap B) \cup X \\
& \Rightarrow \{ \{c\}, \{c,d\} \} \subset \Pwr((A \cap B) \cup X) \\
& \Rightarrow (c,d) \in \Pwr(\Pwr((A \cap B) \cup X)) \\
& \iff (c,d) \in (A \cap B) \times X \\
\end{align*}
Which completes the proof.
\end{proof}
\bigbreak
\begin{proof}(3)
\bigbreak ($\Rightarrow$)
\begin{align*}
(c,d) \in (A - B) \times X & \iff c \in (A-B) \land d \in X \\
& \iff (c \in A \land c \notin B) \land d \in X \\
& \iff (c \in A \land d \in X) \land (c \notin B \land d \in X) \\
(\text{since $c \notin B$} ) \quad & \Rightarrow (c,d) \in A \times X \land (c,d) \notin B \times X\\
& \iff (c,d) \in (A \times X)-(B \times X)\\
\end{align*}
\bigbreak ($\Leftarrow$)
\begin{align*}
(c,d) \in (A \times X)-(B \times X) & \iff (c,d) \in (A \times X) \land (c,d) \notin (B \times X)\\
& \Rightarrow (c \in A \land d \in X) \land (c \notin B \lor d \notin X) \\
(\text{since ($d \in X \land d \notin X$, $\rightarrow \leftarrow$)}) \quad & \Rightarrow (c \in A \land d \in X) \land (c \notin B) \\
&\iff (c \in A \land c \notin B) \land d \in X \\
& \iff c \in (A - B) \land d \in X\\
& \Rightarrow \{ \{c\}, \{c,d\} \} \subset \Pwr((A - B) \cup X) \\
& \iff \{ \{c\}, \{c,d\} \} \in \Pwr(\Pwr((A - B) \cup X)) \\
& \iff (c,d) \in (A - B) \times X \\
\end{align*}
Which completes the proof.
\end{proof}
\bigbreak
\begin{proof}(4)
\bigbreak ($\Rightarrow$) Suppose, without loss of generality, that $A = \emptyset$. Then, $A$ contains no elements. Consider $A \times B = \{(a,b): a \in A \land b \in B\}$. Then, since there are no $a \in A$, $\{(a,b): x \in A \land x \in B\} = \emptyset$.
\bigbreak ($\Leftarrow$) Suppose to the contrary that $A\neq \emptyset$ and $B\neq \emptyset$, but $A \times X = \emptyset$. Since $A\neq \emptyset$ and $B\neq \emptyset$, there exists some $a \in A$ and $b \in B$. And so, $\{ \{a\}, \{a,b\}\} \subset \Pwr(A \cup B)$ and further we have $(a,b) \in A \times B$. However, this is a contradiction since we assumed $A \times B = \emptyset$.
\end{proof}
\bigbreak
\begin{proof} (5)
\bigbreak ($\Rightarrow$)
We show that if $A \subset X$ and $B \subset Y$, then $A \times B \subset X \times Y$. Since $A \subset X$, for all $a \in A$, $a \in X$ and likewise for $B$.
\begin{align*}
(c,d) \in A \times B & \iff c \in A \land d \in B \\
(\text{by Assumption}) \quad & \Rightarrow c \in X \land d \in Y \\
& \Rightarrow c \in X \cup Y \land d \in X \cup Y \\
& \Rightarrow \{ \{c\}, \{c,d\}\} \subset \Pwr(X \cup Y) \\
& \Rightarrow (c,d) \in \Pwr(\Pwr(X \cup Y)) \\
& \iff (c,d) \in X \times Y \\
\end{align*}
\bigbreak ($\Leftarrow$) Suppose that $A \times X \neq \emptyset$. And that$A \times B \subset X \times Y$. We show that $A \subset X$ and $B \subset Y$.
\begin{align*}
a \in A \land b \in B & \Rightarrow \{ \{a\},\{a,b\}\} \in \Pwr(\Pwr(A \cup B)) \\
& \iff (a,b) \in A \times B \\
& \Rightarrow (a,b) \in X \times Y \\
& \Rightarrow (a,b) \in \{(x,y): x \in X \land y \in Y\} \\
& \Rightarrow a \in X \land b \in Y \\
\end{align*}
Which completes the proof.
\end{proof}
\newpage
\begin{mdframed}
\section{Relations}
\end{mdframed}
\begin{exercise} We show that for each of \textbf{symmetric}, \textbf{reflexive}, and \textbf{transitive} properties, there exists a relation that does not have that property but does have the other two.
\end{exercise}
\begin{proof} Let $X$ be a set. We first show that if $X = \emptyset$, then any relation in $X$ is an equivalence relation:
\begin{Lemma} \renewcommand{\qedsymbol}{} \normalfont Let $X = \emptyset$. Then, by a previous theorem, we have $X \times X =\emptyset$. And so, if $R$ is a relation in $X$, $R = \emptyset$. However, $R$ is an equivalence relation, since all statements are vacuously satisfied.
\end{Lemma}
$ $\newline Likewise, suppose that $X = \{a\}$; i.e. $X$ is a singleton. We claim, also that any relation in $X$ is an equivalence relation:
\begin{Lemma} \renewcommand{\qedsymbol}{} \normalfont Let $X = \{a\}$. Then, by the comments of the previous section, we have $X \times X= \{(a,a)\}$. Thus, since $R$ is the set $\{(a,b): a \in X \land b \in X\}$ it follows that $R = \{(a,a)\}$ for any relation.\footnote{see Halmos pg. 27} It is easy to verify that the transitive condition is vacuously satisfied for $R$. And, it is symmetric, since $(a,a) = (a,a)$. And, clearly, $R$ is reflexive. Thus, $R$ is an equivalence relation.
\end{Lemma}
$ $\newline We also show that for $X = \{a,b\}$ each of which is distinct, there does not exist a relation, which is symmetric, reflexive, but not transitive:
\begin{Lemma} \renewcommand{\qedsymbol}{} \normalfont Let $X = \{a,b\}$. Then, the relation $\mathcal{R}$ in question must contain $\{(a,a),(b,b)\} = I$. However, it is easy to verify that this is an equivalence relation.\footnote{see the above lemma} Thus, we must add an element of $X \times X$ which maintains its symmetry, yet is not transitive. However, this is not possible since either way $(a,b)$, $(b,a)$ must be in $\mathcal{R}$ and so we would have $\mathcal{R} = \{(a,a), (b,b), (a,b), (b,a)\}$.And, this is an equivalence relation since $(x,x) \in \mathcal{R}$ for all $x \in X$ and, by the comments above, $ \mathcal{R}$ is symmetric, \textit{as well as} transitive.\footnote{this is left to the reader}
\end{Lemma}
$ $\newline Thus, let $X = \{ a, b, c ....\}$, for distinct elements. We first show the relational properties which include reflexivity: \bigbreak
Let $\mathcal{R}$ be a relation in $X$ which is reflexive. Then, we must have $I = \{(x,x): x \in X\} \subset \mathcal{R}$, by definition. Thus, we show a representation of $\mathcal{R}$ which is transitive, but not symmetric, and symmetric but not transitive:
\begin{itemize}
\item Consider $\mathcal{R} = I \cup \{(a,b), (b,a), (b,c), (c,b)\}$. Then, this relation is symmetric, since $(x,x) = (x,x)$ for all $x \in \mathcal{R}$ and $\{(a,b), (b,a), (b,c), (c,b)\} \subset \mathcal{R}$. However, $\mathcal{R}$ is not transitive, since $(a,b) \in \mathcal{R}$ and $(b,c) \in \mathcal{R}$ and yet $(a,c) \notin \mathcal{R}$.
\item Consider $\mathcal{R} = I \cup \{(a,b)\}$. Then, $\mathcal{R}$ is transitive; note, we only need to check $(a,b)$, $(a,a)$, $(b,b)$ for transitivity, since they are the only ordered pairs which share a first, or second coordinate, where only $(a,a)$, or $(a,b)$ come first. Correctly, $(a,b) \in \mathcal{R}$ and $(b,b) \in \mathcal{R}$ implies $(a,b) \in \mathcal{R}$; $(a,a) \in \mathcal{R}$ and $(a,b) \in \mathcal{R}$ implies $(a,b) \in \mathcal{R}$. However, $\mathcal{R}$ is not symmetric: $(a,b) \in \mathcal{R}$, however, $(b,a) \notin \mathcal{R}$.
\end{itemize}
$ $\newline Finally, we show the relation in $X$ which is not reflexive. Let $X$ be given as above:
\begin{itemize}
\item Consider $\mathcal{R} = \{(a,b), (b,a), (a,a), (b,b)\} \subset X \times X$. This is symmetric since $(x,x) = (x,x)$ for all $x \in X$ and $\{(a,b),(b,a)\} \subset \mathcal{R}$. It is, also, reflexive since $(a,b) \in \mathcal{R}$ and $(b,a) \in \mathcal{R}$ implies $(a,a) \in \mathcal{R}$; likewise, $(b,a) \in \mathcal{R}$ and $(a,b) \in \mathcal{R}$ implies $(b,b) \in \mathcal{R}$.\footnote{the others follow} However, $\mathcal{R}$ is not reflexive since $c \in X$, yet $(c,c) \notin \mathcal{R}$.
\end{itemize}
\end{proof}
\bigbreak
\begin{exercise} We show that the set of all equivalence classes, $X/\mathcal{R}$, is indeed a set.
\end{exercise}
\begin{proof} Let $\mathcal{R}$ be an equivalence relation on a set $X$. We show that $X/ \Rcal \subset \mathscr{P}(X)$:
\begin{align*}
z \in X/\Rcal & \Rightarrow (\exists x \in X)(z = \{x/\Rcal \} = \{y \in X: (x,y) \in \Rcal\} \subset X) \\
& \Rightarrow z \in \mathscr{P}(X) \\
\end{align*}
Which completes the proof.
\end{proof}
\newpage
\begin{mdframed}
\section{Functions}
\end{mdframed}
\begin{exercise}
We show the special cases in which the projections are 1-1.
\end{exercise}
\begin{proof} Without loss of generality, we only consider $g:X \times Y \rightarrow Y$, the range projection.
\begin{itemize}
\item We first note that if $X$, $Y$ have a pair or more of distinct elements, then $g$ is not 1-1:
\begin{lemma} Suppose $X$, $Y$, have more than a pair of distinct elements, then $g$ is not 1-1: To see this, let $\{a,b\} \subset X$, and $\{c,d\}\subset Y$, then $\{(a,c), (a,d), (b,c), (b,d)\} \subset X \times Y$. If we suppose $g$ is one-to-one, then $g((a,c)) = g((b,d))$ implies $(a,c) = (b,d)$. But this is a contradiction, since $a=b$ and yet $a$, $b$ are distinct. \end{lemma}
\item Next, if $X = \{x\}$ and $Y = \{y\}$, then we claim $g$ is 1-1.
\begin{lemma} Let $X = \{x\}$ and $Y = \{y\}$; then, $X \times Y = \{(x,y),(y,x)\}$. Upon inspection, we see that $g$ is 1-1: if $(x,y) \neq (y,x)$, then $y \neq x$ and $y = g((x,y)) \neq x = g((y,x)$. We note that this covers the case in which $x=y$.
\end{lemma}
\item Next, we show that if either $X$ or $Y$ is a singleton and the other is an arbitrary set, $g$ is one-to-one.
\begin{lemma}
Suppose, without loss of generality, that $X$ is the singleton. Then either $Y =\emptyset$ or $Y \neq \emptyset$. If $Y=\emptyset$, then $X \times Y = \emptyset$, by previous exercise; which is trivially 1-1. Else, we assume $Y$ has more than a pair of distinct elements. Since $X = \{x\}$ for some $x$, it follows that $\{(a,b): a\in X \land b \in Y\} = \{(x,b): b \in Y\}$, which means $g$ is 1-1.
\end{lemma}
\item Lastly, if $X = Y = \emptyset$, then all conditions are vacuously satisfied, and so $g$ is 1-1.
\end{itemize}
\end{proof}
\begin{exercise} We show that $Y^{\emptyset}$ has exactly one element, namely $\emptyset$, whether $Y$ is empty or not; i.e. $Y^\emptyset = \{\emptyset \}$.
\end{exercise}
\begin{proof} Suppose that $Y$ is a set. Consider $f = Y^\emptyset$. From page thirty, and by a previous theorem, we have $f \subset \mathscr{P}(\emptyset \times Y) = \mathscr{P}(\emptyset) = \{\emptyset\}$, where $f$ is a set of elements which are ordered pairs. From the comments in section seven, $\emptyset$ is a set of ordered pairs. It follows that $f = \{\emptyset\}$.
\end{proof}
\begin{exercise} We show that if $X \neq \emptyset$, then $\emptyset^X$ is empty; i.e. $\emptyset^X = \emptyset$.
\end{exercise}
\begin{proof}
Suppose that there is some function $f \in \emptyset^X$. Then, for all $x \in X$, there exists some $b \in \emptyset$ such that $(x,b) \in f$. However, this is not true, since $\emptyset$ contains no elements. Thus, $\emptyset^X = \emptyset$.
\end{proof}
\newpage
\begin{mdframed}
\section{Families}
\end{mdframed}
\begin{exercise} After the comments on page thirty-five, we formulate and prove a generalized version of the commutative law for unions.
\end{exercise}
\begin{proposition} Let $K$ be an arbitrary, non-empty set, and let $p \in \normalfont\text{Aut}(K^K)$ be an element of the set of one-to-one and onto functions from $K$ to $K$. We note that in the current notation this means that $p$ is the family and $\{p_i\}$ denotes the values of $p$ evaluating some $i \in K$. Let $\{A_k\}$ be a family of functions with domain $K$. We claim that $\bigcup_{k \in K} A_k = \bigcup_{i \in K} A_{p_i}$.
\end{proposition}
\begin{proof}
\bigbreak $ $\newline ($\Rightarrow$)
\begin{align*}
x \in \bigcup_{k \in K} A_k & \Rightarrow (\exists k_0 \in K)(x \in A_{k_0}) \\
(\text{since $p$ is onto}) \quad& \Rightarrow (x \in A_{k_0}) \land (\exists s \in K)(k_0 = p_s) \\
& \Rightarrow x \in A_{k_0} = A_{p_s} \\
& \Rightarrow x \in \bigcup_{i \in K} A_{p_i} \\
\end{align*}
\bigbreak $ $\newline ($\Leftarrow$)
\begin{align*}
x \in \bigcup_{i \in K} A_{p_i} & \Rightarrow (\exists s \in K)(x \in A_{p_s})\\
(\text{since $p_s \in K$ and onto}) \quad & \Rightarrow (x \in A_{p_s}) \land (\exists k_0 \in K)(p_s = k_0) \\
& \Rightarrow x \in A_{p_s} = A_{k_0}\\
& \Rightarrow x \in \bigcup_{k \in K} A_k \\
\end{align*}
Which completes the proof.
\end{proof}
To illustrate the previous proof, consider $K = \{0,1\}$ and
$p_i = \begin{cases}
1 & i = 0 \\
0 & i = 1 \\
\end{cases}$; it is easy to show that $p$ is 1-1 and onto. From the statement above, we have
\begin{align}
\bigcup_{k \in K} A_k & = A_0 \cup A_1 \\
\bigcup_{i \in K} A_{p_i} & = A_{p_0} \cup A_{p_1} = A_1 \cup A_0
\end{align}
\setcounter{equation}{0}
\begin{exercise} We show that if both $\{A_i\}$ and $\{B_i\}$ are families of sets, with domains $I$, $J$, then
\begin{align}
\Big( \bigcup_i A_i \Big) \cap \Big(\bigcup_j B_j \Big) = \bigcup_{i,j}(A_i \cap B_j) \\
\Big( \bigcap_i A_i \Big) \cup \Big( \bigcap_j B_j \Big) = \bigcap_{i,j}(A_i \cup B_j)
\end{align}
Where the symbols such as $\bigcap_{i,j}$ mean $\bigcap_{(i,j) \in I \times J}$
\end{exercise}
\begin{proof} (1)
\bigbreak $ $\newline ($\iff$)
\begin{align*}
x \in \Big( \bigcup_i A_i \Big) \cap \Big(\bigcup_j B_j \Big) & \iff x \in \Big( \bigcup_i A_i \Big) \land x \in \Big(\bigcup_j B_j \Big) \\
& \iff (\exists i_0 \in I)(x \in A_{i_0}) \land (\exists j_0 \in J)(x \in B_{j_0}) \\
& \iff (\exists (i_0,j_0) \in I \times J)(x \in (A_{i_0} \cap B_{j_0}) )\\
& \iff x \in \bigcup_{i,j}(A_i \cap B_j) \\
\end{align*}
\end{proof}
\begin{proof} (2)
\bigbreak $ $\newline ($\iff$)
\begin{align*}
x \in \Big( \bigcap_i A_i \Big) \cup \Big( \bigcap_j B_j \Big) & \iff x \in \Big( \bigcap_i A_i \Big) \lor x \in \Big( \bigcap_j B_j \Big) \\
& \iff (\forall i \in I)(x \in A_i) \lor (\forall j \in J)(x \in B_j) \\
& \iff (\forall i \in I)(\forall j \in J)(x \in A_i \lor x \in B_j) \\
& \iff (\forall i \in I)(\forall j \in J)(x \in A_i \cup x \in B_j) \\
& \iff (\forall (i,j) \in I\times J) (x \in (A_i \cup B_j)) \\
& \iff x \in \bigcap_{(i,j) \in I \times J} (A_i \cup B_j)\\
\end{align*}
\end{proof}
\setcounter{equation}{0}
\begin{exercise} Let $\{A_i\}$, $\{B_j\}$ be families of sets with domains $I \neq \emptyset$, $J \neq \emptyset$, respectively. We show that
\begin{align}
\Big( \bigcup_i A_i \Big) \times \Big( \bigcup_j B_j \Big) &= \bigcup_{i,j} (A_i \times B_j) \\
\Big( \bigcap_i A_i \Big) \times \Big( \bigcap_j B_j \Big) &= \bigcap_{i,j} (A_i \times B_j)
\end{align}
\end{exercise}
\begin{proof} (1)
\bigbreak $ $\newline ($\iff$)
\begin{align*}
(a,b) \in \Big( \bigcup_i A_i \Big) \times \Big( \bigcup_j B_j \Big) & \iff a \in \bigcup_i A_i \land b \in \bigcup_j B_j \\
& \iff (\exists i_0 \in I)(\exists j_0 \in J)(a \in A_{i_0} \land b \in B_{j_0}) \\
& \iff (\exists (i_0,j_0) \in I \times J)((a,b) \in A_{i_0} \times B_{j_0}) \\
& \iff (a,b) \in \bigcup_{(i,j) \in I \times J} (A_i \times B_j) \\
\end{align*}
\end{proof}
\begin{proof} (2) Suppose that for each $i \in I$, $A_i \neq \emptyset$ and for each $j \in J$, $B_j \neq \emptyset$.
\bigbreak $ $\newline ($\iff$)
\begin{align*}
(a,b) \in \Big( \bigcap_i A_i \Big) \times \Big( \bigcap_j B_j \Big) & \iff a \in \bigcap_i A_i \land b \in \bigcap_j B_j \\
& \iff (\forall i \in I)(a \in A_i) \land (\forall j \in J)(b \in B_j) \\
& \iff (\forall i \in I)(\forall j \in J)(a \in A_i \land b \in B_j)\\
& \iff (\forall i \in I)(\forall j \in J)( (a,b) \in A_i \times B_j ) \\
& \iff (\forall (i,j) \in I \times J)( (a,b) \in A_i \times B_j ) \\
& \iff (a,b) \in \bigcap_{i,j} A_i \times B_j \\
\end{align*}
\end{proof}
\begin{exercise} Suppose that for each $i \in I$, $X_i$ is non-empty. Consider the family of sets $\{X_i\}$ with domain $I$. We show that $\bigcap_i X_i \subset X_j \subset \bigcup_i X_i$ for each index $j \in I$.
\end{exercise}
\begin{proof} Let $\{X_i\}$ be stated as above, and let $j \in I$ be arbitrary.
\begin{align*}
x \in \bigcap_i X_i & \Rightarrow (\forall i \in I)(x \in X_i) \\
& \Rightarrow x \in X_j \quad (\text{since $j \in I$})\\
\end{align*}
Which proves the first inclusion. For the second, suppose $j \in I$ is arbitrary, then we have the following:
\begin{align*}
x \in X_j & \Rightarrow x \in \bigcup_j X_j \\
& \Rightarrow x \in \Big( \bigcup_j X_j \cup \bigcup_{z \in I-J} X_z \Big)\\
& \Rightarrow x \in \bigcup_{i} X_i \\
\end{align*}
Which prove the second inclusion.
\end{proof}
\begin{exercise} We show the minimality condition of intersection and unions: (1) That is, if $X_j \subset Y$ for each index $j$ and some set $Y$, then $\bigcup_i X_i \subset Y$ and that it is unique; (2) Likewise, if $Y \subset \bigcap_j X_j$ for each index $j$ and some set $Y$, then $Y \subset \bigcap_i X_i$ and it is unique.
\end{exercise}
\begin{proof} (1)
Suppose that $\{X_i\}$ is a family of sets with domain $I$, such that $j \in I$, and let $Y$ be a set. Then, we have the following:
\begin{align*}
(\forall j)(X_j \subset Y) & \Rightarrow \bigcup_j X_j \subset Y \\
& \Rightarrow \bigcup_i X_i \subset Y \\
\end{align*}
\end{proof}
\begin{proof} (2)
Suppose that $\{X_i\}$ is a family of sets with domain $I$, such that $j \in I$. And let $Y$ be a set. Then, we have the following:
\begin{align*}
Y \subset \bigcap_j X_j & \Rightarrow Y \subset \bigcap_i X_i\\
\end{align*}
\end{proof}
\newpage
\begin{mdframed}
\section{Inverses and Composites}
\end{mdframed}
\begin{exercise} Suppose that $f: X \rightarrow Y$. Let $\{A_i\}$ be a family of subsets of $X$. Define $f': \mathscr{P}(X) \rightarrow \mathscr{P}(Y)$, as the mapping from each $A_i$ to the image subset, $f'(A_i)$, as stated in the text. We claim that $$f' \Big( \bigcup_i A_i\Big) = \bigcup_i f'(A_i) $$
\end{exercise}
\begin{proof} After the comments on page thirty-four, we note that $A: I \rightarrow \mathscr{P}(X)$, for some index set $I \neq \emptyset$. Then, we have the following:
\bigbreak ($\Rightarrow$)
\begin{align*}
x \in \bigcup_i f'(A_i) & \Rightarrow (\exists i_0 \in I)(x \in f'(A_{i_0})) \\
(\text{since $A_{i_0} \subset \bigcup_i A_i$}) \quad & \Rightarrow x \in f'\Big(\bigcup_i A_i\Big) \\
\end{align*}
\bigbreak ($\Leftarrow$)
\begin{align*}
x \in f' \Big( \bigcup_i A_i\Big) & \Rightarrow (\exists i_0 \in I)(x \in f'(A_{i_0})) \\
& \Rightarrow x \in \Big(\bigcup_{z \in I - \{i_0\}} f'(A_z) \Big) \cup f'(A_{i_0}) = \bigcup_i f'(A_i) \\
\end{align*}
And the result follows.
\end{proof}
\begin{exercise} We show that, in general,
$$f' \Big( \bigcap_i A_i\Big) = \bigcap_i f'(A_i) $$
does not hold.
\end{exercise}
The following proof was suggested by David. H..
\begin{proof} Consider $X = \{a,b,c\}$ and $Y = \{d,e\}$ and suppose all the elements are distinct. Then define $f': \Pwr(X) \rightarrow \Pwr(Y)$ as the following:
\begin{align*}
f'(\emptyset) & = \emptyset \\
f'(\{a\}) & = \{d\} \\
f'(\{b\}) & = \{e\} \\
f'(\{c\}) & = \{d\} \\
f'(\{a,b\})& = \{d,e\} \\
f'(\{b,c\}) & = \{d\} \\
f'(\{a,c\}) & = \{e\} \\
f'(\{a,b,c\})& = \emptyset \\
\end{align*}
Then, let $\{A_i\}$ be a family of subsets of $X$ with domain $I = 2$, such that $A_0 = \{a\}$ and $A_1 = \{a,c\}$. Then, we have the following:
\begin{align*}
f'\Big( \bigcap_i A_i\Big) & = f'(\{a\}) = \{d\} \\
\bigcap_i f'(A_i) & = f'(A_0) \cap f'(A_1) = \{d\} \cap \{e\} = \emptyset \\
\end{align*}
Which completes the proof.
\end{proof}
\begin{exercise} Let $f: X \rightarrow Y$. We show that $f$ maps $X$ onto $Y$ iff for every non-empty subset $B$ of $Y$, $f^{-1}(B) \neq \emptyset$.
\end{exercise}
\begin{proof}
\bigbreak $ $\newline ($\Rightarrow$)